2016
DOI: 10.1080/19443994.2015.1065440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zeolite application on potassium release in sandy soils amended with municipal compost

Abstract: A B S T R A C TThe use of compost in enhancing organic carbon content and aggregation in soil has been widely studied in the last decades. Recently, compost is used in new environmental applications for the remediation of both contaminated groundwater and soil. However, compost addition increases by 10 orders of magnitude the soil electrical conductivity and the nutrient content such as potassium. Subsequently, nutrient leaching in groundwater may increase water salinity. The present study investigates the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Zeolites may also be used to remove inorganic and organic air pollutants, including nitrogen oxides (NOx) and volatile organic compounds (VOCs) [22][23][24]. Finally, they can be used for the removal, fixation, and control of contaminants and transport of nutrients in soils and sediments [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites may also be used to remove inorganic and organic air pollutants, including nitrogen oxides (NOx) and volatile organic compounds (VOCs) [22][23][24]. Finally, they can be used for the removal, fixation, and control of contaminants and transport of nutrients in soils and sediments [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…3(b)). In any case, the enhanced concentration of exchangeable and plant‐available K in both adsorbents is a beneficial property, since K‐loaded zeolites can be used as slow‐release fertilizers, able to reduce the leaching of K in soils or soilless potting media compared to conventional fertilizers 84,85 …”
Section: Resultsmentioning
confidence: 99%
“…The losses of K + by surface runoff and groundwater leaching can be reduced by supplementing the zeolites as slow-release fertilizer [108]. For example, the application of zeolites in municipal compost to investigate the K + release pattern resulted in six times less leaching loss from the zeolitic compost as compared to normal compost [109]. Additionally, Williams and Nelson [110] observed that in a soil-less medium K + saturated clinoptilolite recorded 23% less leaching of K + over-controlled control substrate.…”
Section: Nutrient Retentionmentioning
confidence: 99%
“…Additionally, Williams and Nelson [110] observed that in a soil-less medium K + saturated clinoptilolite recorded 23% less leaching of K + over-controlled control substrate. Moraetis et al [109] reported that there was 18-fold increase in bioavailable K when zeolites were added through kinetic experiment to the soil-compost mixture, suggesting high potassium affinity in the soilcompost-zeolite mixture. Zeolite is considered as nano-enhanced green application as it adsorbs molecules at relatively low pressure [111,112].…”
Section: Nutrient Retentionmentioning
confidence: 99%